Benjamin Franklin, Jonathan Edwards, and the representation of American culture - Oberg, Barbara; Stout, Harry S. (Oxford University Press, 1993)
This is an interdisciplinary collection of comparative essays which looks at aspects of the thought of Edwards and Franklin and considers their places in American culture.